The Association of Age and Gender with the Histopathological Features among Thyroid Cancer Patients in Erbil City, Iraq: Clinical Analysis of 153 Cases - Awla, Harem Khdir; Saleh, Lana Sardar (Iraqi Journal of Science, 2023)
Background: Thyroid cancer (TC) is an increasingly prevalent malignancy throughout the world. It has long been recognized that the incidence of TC is higher in women which increases with age. However, the association of gender disparity and age with TC aggressiveness and outcomes are still controversial. The aim of this study was focused on the association of age and gender with histopathological characteristics in TC. Methods: 153 patients who met the criteria, were selected.  The included cases were divided into four age groups (≤24 years, 25-44 years, 45-64 years, and ≥65 years). Demographic, age and pathological parameters were compared among them. The association of gender and age with histopathological features were then evaluated. Results: Females were significantly more frequent in almost all age groups with the highest female frequency found the age group of 25-44 years old. Females are more susceptible for TC even when they are young. The four groups showed highly significant differences regarding extrathyroidal extension (ETE) which is more aggressive in older individuals’ tumor. However, there were no significant differences regarding tumor size, multifocality, LV invasion and LN metastasis. Moreover, increasing age was significantly associated with increases risk of ETE. In addition, old patients and males were significantly more likely to have larger tumor size. Nonetheless, both gender and age non-significantly associated with multifocality and LV invasion. Conclusion: Our results confirmed that increasing age could really exert a negative prognostic effect, at least in terms of ETE risk and larger tumor size. In addition, TC risk in females was more frequent in all age groups and significantly more likely than men to present at younger, nonetheless, males represented larger tumor size.